ASME 2015 13th International Conference on Nanochannels, Microchannels, and Minichannels 2015
DOI: 10.1115/icnmm2015-48031
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of a Novel Pulsating Heat Pipe Cooler for Power Electronics at Extreme Ambient Temperatures

Abstract: A compact and low cost pulsating heat pipe cooler (PHP) based on automotive technology is presented. This technology uses numerous aluminium MultiPort Extruded (MPE) tubes with capillary sized channels disposed in parallel to achieve the desired compactness. The sub-channels of the MPEs are connected in a serpentine manner by means of fluid distribution elements integrated in the evaporator and condenser manifolds. This configuration enables the oscillation of liquid slugs and elongated bubbles between the eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…D. Torresin et al [26]. In this paper the test outcomes of an open loop type PHP with refrigerating fluids R134a and R245fa are observed.…”
Section: Effect Of Refrigerants As Working Fluidmentioning
confidence: 69%
See 1 more Smart Citation
“…D. Torresin et al [26]. In this paper the test outcomes of an open loop type PHP with refrigerating fluids R134a and R245fa are observed.…”
Section: Effect Of Refrigerants As Working Fluidmentioning
confidence: 69%
“…4. R134a Heat Load vs Maximum Thermal Resistance [26] From Fig 4 it tends to be seen,the PHP cooler is working for all the tried air temperature-conditions in the scope of heat load structure 500 to 1750 W. The maximum thermal resistance remains practically steady for air temperatures between -20 °C and 40 °C in the whole scope of tried warmth loads. At -60 °C and 60 °C air temperatures, a sharp increment of the most extreme warm obstruction is watched for heat loads higher than 1.5 kW.…”
Section: Effect Of Refrigerants As Working Fluidmentioning
confidence: 88%
“…They concluded that the optimal filling ratio did not change with the power input in the range of temperature explored and they identified better performance for a specific condenser temperature (193 K). the optimal filling ratio is a function of the thermal properties of the working fluid, as demonstrated by Torresin et al [13], where the authors carried out an experimental characterization of an open-loop PHP for automotive applications in a climatic chamber (controlled atmospheric temperature between 213 K to 333K), with fixed cooling airflow and heat power density ranging between 3 and 13 W/cm 2 . Indeed, for the two fluids tested (R134a and R245fa), different optimal filling ratio has been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, for the two fluids tested (R134a and R245fa), different optimal filling ratio has been identified. In both [12] and [13] the authors highlight the critical role of the viscosity, which can lead to degradation of the thermal performance of the PHP. It is then important to explore wider temperature ranges for commonly used fluids in PHPs and observe their functioning and potential limitations caused by viscous dissipation.…”
Section: Introductionmentioning
confidence: 99%